Substitution:
2x + (6(1/2x - 6)) = 19
2x + 3x - 36 = 19
5x - 36 = 19
+ 36
5x = 55
÷ 5
x = 11
y = (1/2 × 11) - 6
y = 5.5 - 6
y = -0.5
Elimination:
y = 1/2x - 6
- y
0 = 1/2x - 6 - y
+ 6
1/2x - y = 6
3x - 6y = 36
2x + 6y = 19
(add)
5x = 55
÷ 5
x = 11
y = (1/2 × 11) - 6
y = 5.5 - 6
y = -0.5
I hope this helps! Let me know if you need me to explain why I did some things :)
Answer:
15
Step-by-step explanation:
Angle 2 is 2x+10
angle 4 is 4x+80
and from the figure we can understand that when we add these 2 equations
We get
6x+ 90= 180
6x = 180 - 90= 90
6x= 90
x = 90 ÷ 6 = 15
answer = 15
Answer:
what do u want us to do?
Step-by-step explanation:
Answer:
21
Step-by-step explanation:
Answer:
-(20+z)/y = x
Step-by-step explanation:
-20=xy +z
Subtract z from each side
-20 -z = xy+z-z
-20 -z = xy
Divide each side by y
(-20 -z)/y = xy/y
Factor out a negative
-(20+z)/y = x